FACTORS FOR THE OCCURRENCE OF DENGUE HEMORRHAGIC FEVER AT THE KEMILING INPATIENT HEALTH CENTER IN BANDAR LAMPUNG - Nur Alam Virdaus Sujana; Samino Samino; Agung Aji Pedana (HEARTY, 2026)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that remains a major public health problem in many tropical regions, including Indonesia. This study aims to analyze the factors influencing the incidence of DHF, including Mosquito Breeding Eradication Behavior (PSN), community participation, the use of bed nets, the use of window screens, and support from health workers. The research method used an observational analytic approach with a case-control design. A total sample of 75 respondents consisted of 25 in the case group and 50 in the control group. Statistical tests were conducted using univariate analysis, bivariate chi-square, and multivariate logistic regression. The results showed that poor PSN behavior was more frequently found in DHF cases (65.2%) compared to controls (34.8%), while good PSN behavior was dominant in controls (78.8%) compared to cases (21.2%). Support from health workers was more often received by controls (72.4%) than cases (27.6%). Both good and poor community participation were more dominant in the control group, 86.4% and 56.6% respectively. The use of window screens and bed nets was also higher among controls, 76.6% and 85.7%, compared to cases, 23.4% and 14.3% respectively. Analysis showed a significant relationship between PSN behavior (p=0.001; OR=6.98), community participation (p=0.028; OR=4.85), the use of window screens (p=0.016; OR=3.77), the use of bed nets (p=0.041; OR=4.45), and support from health workers (p=0.037; OR=3.75) with DHF incidence. PSN behavior was identified as the dominant factor with OR=4.317 in the UPT Puskesmas Rawat Inap Kemiling, Bandar Lampung, in 2025. Conclusion: PSN behavior, community participation, use of window screens, use of bed nets, and support from health workers were significantly associated with DHF incidence, with PSN behavior as the dominant factor. Recommendation: Educational institutions should regularly provide PSN education, implement environmental sanitation programs, and integrate DHF materials into curricula, while health centers need to enhance socialization, cadre training, and prevention facilities. All these efforts aim to create sustainable interventions to reduce DHF incidence.